The Effect of Agility and Speed on Ability Basketball Dribble for Extracurricular Students SMP Negeri 44 Palembang - Resti Anita; Bayu Hardiyono (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2023)
This study aims to determine how much influence agility and speed have on basketball dribbling skills in extracurricular students of SMP Negeri 44 Palembang. This research method uses quantitative path analysis method. The population in this study were all students who took part in basketball extracurricular activities at SMP Negeri 44 Palembang, totaling 20 people. The method of determining the sample is by using a saturated sampling technique, totaling 20 people. The data collection technique in this study used a basketball dribble test. Based on the results of the research and discussion in the previous chapter, it is concluded as follows: 1) There is an influence of agility on basketball dribble on students of SMP Negeri 44 Palembang with the percentage of influence being 18.9%. 2) There is an effect of speed on basketball dribble for students of SMP Negeri 44 Palembang with the percentage of influence being 26.4%. It can be concluded that there is an effect of agility and speed on basketball dribbling abilities in extracurricular students of SMP Negeri 44 Palembang.